Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

3(6p-1)=11p-45 heeelp

Sagot :

Answer:

p = -6

Step-by-step explanation:

pls give brainliest if im right

Answer:

multiply 3 from 6p and -1

18p - 3 = 11p - 45

18p - 11p = -45 + 3

7p = - 42 cut 42 by 7 in 6 times 7x6= 42

p= -6 is answer... ❤️